2021
DOI: 10.3390/w13233375
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Low Impact Development Facility Chain on Storm Rainfall Control: A Case Study in Shenzhen, China

Abstract: In recent decades, low impact development (LID) has become an increasingly important concern as a state-of-the-art stormwater management mode to treat urban flood, preferable to conventional urban drainage systems. However, the effects of the combined use of different LID facilities on urban flooding have not been fully investigated under different rainfall characteristics. In this study, a residential, neighborhood-scale catchment in Shenzhen City, southern China was selected as a case study, where the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Then, they compared three scenarios with different combinations, demonstrating that the implementation of green roofs and rainwater revisors had the most significant results for stormwater management. Zhang et al [77] adopted the SWMM model to test two scenarios in Chinese residential areas: (1) the traditional drainage system without sponge facilities; and (2) the drainage system with sponge facilities, i.e., bio-retention cells, permeable pavements, rainwater garden, and grassed pitches. They demonstrated that the combined system was able to reduce a storm with a five-year recurrence interval while also maintaining water quality.…”
Section: Discussionmentioning
confidence: 99%
“…Then, they compared three scenarios with different combinations, demonstrating that the implementation of green roofs and rainwater revisors had the most significant results for stormwater management. Zhang et al [77] adopted the SWMM model to test two scenarios in Chinese residential areas: (1) the traditional drainage system without sponge facilities; and (2) the drainage system with sponge facilities, i.e., bio-retention cells, permeable pavements, rainwater garden, and grassed pitches. They demonstrated that the combined system was able to reduce a storm with a five-year recurrence interval while also maintaining water quality.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have examined the influence of external factors such as confluence relationship [48], terrain slope [49], and pre-conditions [50] on the effectiveness of LID measures, and the research results have enriched the scope of LIDbased frameworks. Several investigators have also verified the effectiveness of LID-based measures in the established LID research areas such as Beijing [51], Guangxi [41], and Shenzhen [52]. Institutional Review Board Statement: Not applicable.…”
Section: Stage Abstract (Frequency/centrality)mentioning
confidence: 99%
“…The stormwater management model (SWMM) has largely been adopted to determine the spatial layout of LID, analyze the hydrological regulation effect of LID, and explore the relationship between LID layouts and runoff paths. ,, The spatial layout of LID affects the control efficiencies of runoff and waterlogging in urban areas . In existing studies, the spatial layout of LID has been optimized in terms of catchments, subcatchments, microcatchments, or grids, and the spatial optimization of LID under precipitation uncertainty has been explored. ,, Site characteristics, such as land cover and land use are the basis of LID spatial optimization.…”
Section: Introductionmentioning
confidence: 99%